Case report: Two-step lamellar keratoplasty for alkali burns - Fang, Xie; Xie, Zhiwen; Luo, Shunrong; Xiao, Xianwen; Yang, Zhengwei; Lin, Yuan; Wu, Huping (Frontiers in Medicine, 2024)
Purpose: To report a case of a patient with ocular surface alkali burn who developed corneal perforation before entering a stable phase. This patient was treated with a custom-designed lamellar graft using a Two-Step lamellar keratoplasty (LK) after 3 months alkali burn. Methods: This study was a case report. Results: A 43-year-old male patient who presented with redness, pain, and decreased vision in his left eye following lime exposure. Initial treatment involved amniotic membrane transplantation and anterior chamber irrigation. However, the patient subsequently developed corneal infiltration and progressive thinning. The patient refused the corneal transplantation and ultimately underwent tarsorrhaphy. Twenty days postoperatively, the patient experienced sudden ocular pain and central corneal perforation. Considering the potential complications of conventional corneal transplantation, including stem cell deficiency, graft dissolution, and rejection, a personalized Two-Step LK was devised. Following this procedure, the patient’s vision gradually improved to 20/133 (without correction), with a good corneal condition but mild epithelial defects and edema. At the 8-month follow-up, subepithelial corneal haze was observed, but uncorrected visual acuity remained stable at 20/133 and best corrected visual acuity was up to 20/66. Conclusions: For patients with ocular surface alkali burns who experience persistent disease progression despite early and mid-stage aggressive interventions, this study is the first to report on the use of a Two-Step LK. This approach takes into account both the "soil" factors that may lead to graft dissolution and the "seed" factors related to recipient stem cell deficiency. The results in preventing graft dissolution and maintaining postoperative corneal function are encouraging.